E-commerce and Financial Performance: Identification on Trends, Benefits and Challenges - Noor, Laili Savitri; Deriawan, Deriawan; Oktrivina, Amelia (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study explores the relationship between e-commerce adoption and financial performance, focusing on how operational benefits such as cost reduction and market expansion translate into economic gains. It also examines the challenges that hinder these benefits and the contextual factors influencing e-commerce effectiveness. The research utilizes a systematic literature review to analyze existing studies on e-commerce, operational efficiency, and financial performance. A contextual framework is proposed to assess the impact of market maturity, consumer behavior, and regulatory environments on e-commerce outcomes. The findings reveal that e-commerce has the potential to enhance operational efficiency and profitability significantly. However, these benefits are only sometimes directly reflected in financial performance due to challenges like cybersecurity risks and technological integration issues. The study also emphasizes that contextual factors like market maturity and consumer preferences have a significant impact on the success of e-commerce strategies. Considering these factors, a tailored approach to e-commerce is essential for maximizing financial returns. The study offers practical insights for managers, emphasizing the need for context-specific e-commerce strategies and the urgency of investments in cybersecurity. It also provides a foundation for future research, suggesting the exploration of industry-specific e-commerce strategies and the long-term impact of digital adoption on financial performance across various economic conditions.